2013
DOI: 10.5858/arpa.2012-0136-oa
|View full text |Cite
|
Sign up to set email alerts
|

Utility and Diagnostic Accuracy of Ureteroscopic Biopsy in Upper Tract Urothelial Carcinoma

Abstract: Context.-Ureteroscopic biopsy is the gold standard for the histopathologic diagnosis of urothelial carcinoma of the upper urinary tract.Objective.-To assess the accuracy of endoscopically obtained biopsy samples in diagnosing, grading, and staging urothelial carcinoma and correlate diagnostic findings to biopsy sample size.Design.-We retrospectively reviewed endoscopic biopsies of the ureter, renal pelvis, and ureteropelvic junction from 2008 to 2011. Biopsy diagnoses that were discordant with follow-up pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 24 publications
2
33
1
Order By: Relevance
“…This is higher than approximately 83%-94% histologic diagnosis yield in endoscopic biopsy series for UTUC. [5][6][7] Notably, elevated BMI was also not associated with decreased success or diagnostic yield in our series. Both CT and US guided techniques had equal success with obtaining tissue for diagnosis, although this was after a radiologist chose the preferred guidance modality based on lesion characteristics and therefore might not be fully generalizable.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…This is higher than approximately 83%-94% histologic diagnosis yield in endoscopic biopsy series for UTUC. [5][6][7] Notably, elevated BMI was also not associated with decreased success or diagnostic yield in our series. Both CT and US guided techniques had equal success with obtaining tissue for diagnosis, although this was after a radiologist chose the preferred guidance modality based on lesion characteristics and therefore might not be fully generalizable.…”
Section: Discussionmentioning
confidence: 41%
“…Ureteroscopic biopsy, the usual approach to obtain tissue in suspected UTUC, has many limitations and a 83%-94% sensitivity for the histologic diagnosis of UTUC. [5][6][7] On the other hand, grade concordance of ureteroscopic biopsy with RNU is generally lower, estimated around 70%. [5][6][7][8][9][10] This stems from limitations in the size of tissue fragments able to be ureteroscopically extracted.…”
mentioning
confidence: 99%
“…Other series have shown that larger biopsy specimens tend to correlate well with the grade of the final specimen. 17 Although not specifically evaluated in this study, in our experience, we have found that the basket does not limit the deflection of the flexible ureteroscope as much as the forceps (Fig. 3).…”
Section: Discussionmentioning
confidence: 70%
“…Muscularis propria is rarely present in upper tract biopsies, and some biopsies may be so superficialthat only epithelium is present, precluding assessment of invasion. In the study by Vashistha et al, they reported a pT stage concordance of 60% for biopsies in which a stage was designated (20). The ureter (59.3%) and renal pelvis (62.5%) had similar pT stage concordance for biopsies.…”
Section: Correlation Between Biopsy Tumor Stage and Resection Tumor Smentioning
confidence: 95%